Sustainability concepts in Malay and Aceh traditional houses - Abdul Majid, Noor Hanita; Denan, Zuraini; Abdul Rahim, Zaiton; Mohd Nawawi, Norwina; Hazman, Siti Norfakiah (Journal of the Malaysian Institute of Planners, 2017)
The migration of people between Acheh and Malaysia can be seen in sporadic settlements in the northern regions. Both communities share Islam as a religion and might have similarities in culture, ethics and the environment. Due to the Islamic influences in both Malay and Aceh community, it is predicted that the traditional houses in both locations are manifestations of the sustainable concept of hablumminallah, hablumminannas and hablumminal'alam. This concept can be analysed in terms of the Islamic implementations of hablumminallah, social beliefs, and activities in the relationship between man and man (hablumminannas) and climatic influences in the relationship between man and environment (hablumminal'alam). Hence, this paper intends to investigate the implementation of the three concepts in the Malay and Aceh houses. The research methodologies employed are observation (through site visits), pictorial analysis and detail evaluations on the components of the houses. Analysis conducted on Rumah Kutai (RK), Perak and Rumoh Aceh (RA) suggest the realization of the three mentioned sustainable concepts in the houses. In conclusion, the overall findings confirmed the sustainability concepts adopted in the RK and RA through adhering to Islamic guidelines, socio-cultural and climatic aspects.